2000
DOI: 10.1093/emboj/19.21.5845
|View full text |Cite
|
Sign up to set email alerts
|

The zinc finger protein Gfi-1 can enhance STAT3 signaling by interacting with the STAT3 inhibitor PIAS3

Abstract: contributed equally to this work STAT factors act as signal transducers of cytokine receptors and transcriptionally activate speci®c target genes. The recently discovered protein PIAS3 binds directly to STAT3 and blocks transcriptional activation. Here, we present experimental evidence implementing the zinc ®nger protein G®-1 as a new regulatory factor in STAT3-mediated signal transduction. The interaction between the two proteins ®rst became evident in a yeast two-hybrid screen but was also seen in coprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 42 publications
(68 reference statements)
5
116
1
2
Order By: Relevance
“…5D). This observation coincides with previous reports that showed that PIAS3 accumulates in dot structures, also called nuclear granules (30,31). The experiments show that the recombinantly expressed and purified rPP-C8 peptides quickly enter cells upon addition to the medium.…”
Section: Expression Purification and Cellular Delivery Of Rpp-c8supporting
confidence: 92%
“…5D). This observation coincides with previous reports that showed that PIAS3 accumulates in dot structures, also called nuclear granules (30,31). The experiments show that the recombinantly expressed and purified rPP-C8 peptides quickly enter cells upon addition to the medium.…”
Section: Expression Purification and Cellular Delivery Of Rpp-c8supporting
confidence: 92%
“…Analysis of Flt3 + DC progenitors revealed a cell-autonomous role for Gfi1 in the activation of STAT3, suggesting that it may act downstream of Ikaros or PU.1. One proposed mechanism is through its ability to inhibit PIAS3 (protein inhibitor of activated STAT3), a specific inhibitor of STAT3 [81]. In this model, loss of Gfi1 leads to the maintenance of PIAS3 activity and thus a reduction in transcriptional events mediated by STAT3.…”
Section: Factors Regulating Early DC Progenitor Developmentmentioning
confidence: 99%
“…These include nuclear hormone receptors, such as the androgen receptor (AR), p53, Smad4, Sp3, HMGI-C, Gfi-1, IRF-1, TFII-I and yeast septins (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). In mouse and man, four Pias genes (Pias1, Pias3, Piasx, and Piasy) have been identified, which encode proteins that share a similar domain structure but differ in their specificity of interaction with other proteins.…”
Section: Piasy-deficient Mice Display Modest Defects In Ifn Andmentioning
confidence: 99%
“…Total RNA was isolated with TRIzol (Invitrogen Life Technologies) and 2 g of RNA were transcribed to cDNA using 200 U SuperscriptII (Invitrogen Life Technologies) and 0.1 nM oligo(dT) [12][13][14][15][16][17][18] in a total volume of 20 l. For one real-time reaction, 2ϫ SYBR Green Mix (Applied Biosystems) was supplemented with 1/40 of synthesized cDNA in addition to the appropriate oligonucleotide primer pair and run on the AbiPrism 7000 sequence detection system (Applied Biosystems, Foster City, CA). Reverse transcriptase controls were done in parallel without adding enzyme.…”
Section: Sybr-green Based Real-time Pcrmentioning
confidence: 99%